EMOTIONAL ASPECTS AND QUALITY OF LIFE IN PATIENTS WITH DEMYELINATING ILLNESSES: THE CASE OF MULTIPLE SCLEROSIS - Arbinaga Ibarzábal, Félix (Anales de Psicología / Annals of Psychology, 2003)
The paper is going to show the characteristics of a group of 17 patients with Multiple Sclerosis in aspects such as depression, anxiety, anxiety sensitivity and the quality of life as related to health. Through the use of the Beck Depression Inventory (BDI) we can see that 58.8% show some level of depression; with higher points than the normative population (p<0.05). They also reflect higher values in anxiety sensitivity, measured with the Anxiety Sensitivity Index (ASI). The average obtained in the EVA Tariff on the questionnaire about the Euroqol Quality of Life (EQ5D) was 0.5859 (+ 0.2182), very inferior to the value obtained in the general population; that is, the subjects with Multiple Sclerosis showed a worse quality of life as related to health. Some significative correlations between depression and anxiety state (measured with the State Trait Anxiety Inventory STAI) and the values of the Euroqol Questionnaire were also shown.